2014
DOI: 10.1089/neu.2013.3128
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Heart Rate and Blood Pressure Increase the Positive Predictive Value of the Glasgow Coma Scale for High-Mortality Traumatic Brain Injury

Abstract: We hypothesized that vital signs could be used to improve the association between a trauma patient's prehospital Glasgow Coma Scale (GCS) score and his or her clinical condition. Previously, abnormally low and high blood pressures have both been associated with higher mortality for patients with traumatic brain injury (TBI). We undertook a retrospective analysis of 1384 adult prehospital trauma patients. Vital-sign data were electronically archived and analyzed. We examined the relative risk of severe head Abb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Hence, the combination of pSBP and pHR could be helpful to predict LT-BI among patients without eye opening, as Reisner et al reported that patients with abnormal SBP, HR, and GCS in the prehospital setting were significantly more likely to have high mortality compared with the single parameter in TBI patients [12]. Our results showed that even subjects with the highest pSBP and lowest pHR had a positive predictive value of 0.61 and an adjusted odds ratio of only 4.77 versus the reference group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the combination of pSBP and pHR could be helpful to predict LT-BI among patients without eye opening, as Reisner et al reported that patients with abnormal SBP, HR, and GCS in the prehospital setting were significantly more likely to have high mortality compared with the single parameter in TBI patients [12]. Our results showed that even subjects with the highest pSBP and lowest pHR had a positive predictive value of 0.61 and an adjusted odds ratio of only 4.77 versus the reference group.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, many investigators reported the prognostic factors or models in TBI patients at an early stage after injury using vital signs, including GCS or pupillary reaction [4, 5, 12, 14, 15]. Among them, either prehospital hypertension or prehospital hypotension were revealed to be associated with higher mortality due to possible intracranial hypertension or paroxysmal sympathetic hyperactivity and impaired cerebral blood flow [3–5, 12]. To the best of our knowledge, our investigation is the first to describe Cushing’s sign in the prehospital setting predicting a life-threatening condition in TBI patients.…”
Section: Discussionmentioning
confidence: 99%
“…AIS) is the basis for assessing the severity of the head injury. Similarly, while the AIS value is low, the GCS is also low[12].…”
mentioning
confidence: 94%
“…A patient's BP is useful when assessing for organ perfusion, identifying stroke risk, and diagnosing sepsis. 1 Studies suggest that it may also provide insight into patient outcome following trauma 2 and has prognostic value in patient mortality. 3 Abbreviations: ANOVA: analysis of variance BMI: body mass index BP: blood pressure EMR: electronic medical record EMS: Emergency Medical Services IA: intra-arterial ICP: intracranial pressure ICU: intensive care unit LAR: Legal Authorized Representative LOA: limits of agreement NIBP: non-invasive blood pressure RIBP: radial intra-arterial blood pressure SBP: systolic blood pressure Though it is recognized as a valuable component in the initial screening assessment, BP remains one of the most difficult vital signs to obtain accurately.…”
Section: Introductionmentioning
confidence: 99%